Effects of soybean meal replacement with dried distillers grains on Boer goat growth performance, feed efficiency, and carcass composition - Beauchamp, Madison; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Dried distillers grain with solubles (DDGS) provides more economical replacement for soybean meal (SBM) in many growing animals diets. While research has been done on the effects of SBM replacement with DDGS in other meat providing species, there is very little research on the effects of soybean replacement on the Boer goat performance. The objective of this experiment evaluates the efficacy of corn dried distiller’s grains with the solubles as a replacement for soybean meal in a Boer goat diet. 48 meat Boer goat kids were randomly separated into 16 pens with 3 kids/pen. Each pen was assigned one of four treatments: 0%, 33%, 66%, and 100% of SBM replaced with DDGS with 4 replicates per treatment. All diets were pelleted and formulated so no supplemental forage was necessary. A step-up period of 14 days was utilized to help gradually introduce the feedstuff to the goats, and help the rumen adapt successfully. The goats were fed for 47 days with growth (ADG, ADFI, G: F) being recorded and calculated. After the growth period 2 out of 3 goats in the pen were randomly selected for slaughter, and carcass composition (carcass weight, yield, loin eye area, 13th rib fat depth, fatty acid profile) was also found. At the end of the experiment it was found that DDGS did in fact provide a nutritionally adequate substitute for soybean meal with no statistical differences being found in either ADG or ADFI. An improvement was seen when comparing gain to feed ratios with statistically separate groups being formed between goats being fed lower amount of DDGS and higher amounts of DDGS (P= 0.001). Trends also began to appear when analyzing the carcass compositions suggesting that the goats fed DDGS instead of SBM had higher final weights. While this is not statistically significant it is biologically relevant especially to producers and the goats economical value. Future experiments utilizing a greater goat number would help confirm this hypothesis statistically.
Keywords: Spring 2018